The effectiveness of Virkon® S disinfectant against an invasive insect and implications for Antarctic biosecurity practices - Bartlett, Jesamine C; Radcliffe, Richard James; Convey, Pete; Hughes, Kevin A; Hayward, Scott A L (Antarctic Science, 2021)
The flightless midge Eretmoptera murphyi is thought to be continuing its invasion of Signy Island via the treads of personnel boots. Current boot-wash biosecurity protocols in the Antarctic region rely on microbial biocides, primarily Virkon® S. As pesticides have limited approval for use in the Antarctic Treaty area, we investigated the efficacy of Virkon® S in controlling the spread of E. murphyi using boot-wash simulations and maximum threshold exposures. We found that E. murphyi tolerates over 8 h of submergence in 1% Virkon® S. Higher concentrations increased effectiveness, but larvae still exhibited > 50% survival after 5 h in 10% Virkon® S. Salt and hot water treatments (without Virkon® S) were explored as possible alternatives. Salt water proved ineffective, with mortality only in first-instar larvae across multi-day exposures. Larvae experienced 100% mortality when exposed for 10 s to 50°C water, but they showed complete survival at 45°C. Given that current boot-wash protocols alone are an ineffective control of this invasive insect, we advocate hot water (> 50°C) to remove soil, followed by Virkon® S as a microbial biocide on ‘clean’ boots. Implications for the spread of invasive invertebrates as a result of increased human activity in the Antarctic region are discussed.
Publisher: Cambridge University Press
Keywords: Antarktis; biologi; biosikkerhet; fjærmygg; forurensning; klimaendringer; miljøpåvirkning; økologi; økosystemer

Antarctic Futures: An Assessment of Climate-Driven Changes in Ecosystem Structure, Function, and Service Provisioning in the Southern Ocean - Rogers, Alex David; Frinault, Betina A V; Barnes, D K A; Bindoff, Nathaniel Lee; Downie, Rod; Ducklow, Hugh W; Friedlaender, A S; Hart, T; Hill, Simeon; Hofmann, E E; Linse, Katrin; McMahon, Clive R; et al. (Annual Review of Marine Science, 2020)
In this article, we analyze the impacts of climate change on Antarctic marine ecosystems. Observations demonstrate large-scale changes in the physical variables and circulation of the Southern Ocean driven by warming, stratospheric ozone depletion, and a positive Southern Annular Mode. Alterations in the physical environment are driving change through all levels of Antarctic marine food webs, which differ regionally. The distributions of key species, such as Antarctic krill, are also changing. Differential responses among predators reflect differences in species ecology. The impacts of climate change on Antarctic biodiversity will likely vary for different communities and depend on species range. Coastal communities and those of sub-Antarctic islands, especially range-restricted endemic communities, will likely suffer the greatest negative consequences of climate change. Simultaneously, ecosystem services in the Southern Ocean will likely increase. Such decoupling of ecosystem services and endemic species will require consideration in the management of human activities such as fishing in Antarctic marine ecosystems.
Keywords: Sørishavet; biodiversitet; klimaendringer; marine økosystemer; miljøpåvirkning

The impact of human activities on wilderness and aesthetic values in Antarctica - Summerson, Rupert; Bishop, Ian D. (Polar Research, 2012)
There has been little progress in implementing protection of wilderness and aesthetic values in Antarctica since the coming into force of the Protocol on Environmental Protection to the Antarctic Treaty in 1998. This can in part be attributed to a lack of research defining these values and showing how they may be assessed. In 2009, a survey comprising 90 images of Antarctic landscapes was established on the Internet to canvass as wide a cross-section of people with an interest in Antarctica as possible on their perceptions of wilderness and their aesthetic preference. At the time of writing, over 337 respondents from 23 nationalities have taken part in the survey. Responses were analysed to determine the effect of human presence, both transient and as infrastructure, on perceptions of wilderness and aesthetic values. The analysis was in three parts: (1) all images combined; (2) images grouped by landscape type, derived from the Environmental Domains of Antarctica regionalization; and (3) 16 pairs of digitally manipulated images of which respondents were shown either an original image or one in which human presence had been either digitally removed or added. Responses to images grouped by landscape type show that coastal and ice-free areas are less valued both aesthetically and as wilderness than mountainous and ice-covered terrains. Signs of human presence were found to make images significantly less likely to be considered as wilderness and also reduced their aesthetic rating. This demonstrates that human impacts on these values are measureable. Keywords: Antarctica; Madrid Protocol; wilderness; aesthetic; values; photographs.
Keywords: Antarktis; Antarktistraktaten; estetikk; menneskelig påvirkning; miljøpåvirkning; miljøvern

The Committee for Environmental Protection: Its Establishment, Operation and Role within the Antarctic Treaty System - Orheim, Olav (Implementing the Environmental Protection Regime for the Antarctic, 2000)
Keywords: Antarktis; miljø; miljøkonsekvensanalyser; miljøpåvirkning